Dirasat in Economics and Business TOWARD AN ISLAMIC BANKING THEORY - Abdussalam, Dr. Ali A. (Dirasat in Economics and Business, 1979)
solve the economic problems confronting it according to its own philosophy. That is, each society tries to choose the economic system which is consistent with its ideology. Both capitalist and socialist countries have devised certain rules of conduct that, by and large, are consis tent with their values. But if we look at the Islamic world it is not hard to discover that a gap exists between the prevailing institutional framework and the Islamic principles. Several fac tors have contributed to this schizophrenic situation. Some of these factors are exogenous while others are indigenous.